Matriz de maturidade lean, bim e green: um mapeamento sistemático de 2008 a 2018 - Carvalho, Mayana Chagas; Santos, Débora de Gois (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The search for competitive strategies has aroused the interest for process improvements in several sectors of the economy. In this sense, many maturity models (MM) have been developed and applied as an organizational management tool, including for the Architecture, Engineering and Construction Industry (AEC). In the literature, some of the models for the construction industry already analyze concepts of Lean Construction, Green and Building Information Model (BIM) separately or two by two, but there are few studies that relate the three concepts. In this way, this article aims to identify scientific publications that relate maturity matrix with the Lean, BIM and Green concepts separately and in combination. Thus, from the systematic mapping of the literature were found 105 scientific publications indexed in the bases of Compendex ™, Scopus®, and Web of Science ™. By the distribution of the publications by levels, a trend of concentration of the researches in models of maturity that approach these concepts of individualized way was perceived. In this way, it is evident that there is knowledge gap, mainly, regarding the maturity matrix approach involving the three concepts.